Unpaid overtime in Greece. Determining factors and theoretical explanations - Ιωαννίδης Αλέξης; Οξούζη Ελένη; Μαυρουδέας Σταύρος (The Greek Review of Social Research, 2013)
The rising of unpaid overtime is a recent trend in West Europe’s and North American labour markets. This phenomenon asks for explanation, since unpaid labour is not consistent with the prevalent economic paradigm. Various theoretical explanations have been proposed by the literature, within or outside the neoclassical framework, backed up with empirical testing. In this article, a literature review and an assessment of these explanations is offered, followed by an empirical investigation of the determinants of unpaid overtime for the Greek laborers. Based on these findings, theoretical conclusions and policy suggestions are been drawn.